The current state of smart tourism research: a bibliometric analysis - Wei, Gan Jia; Ab-Rahim, Rossazana (Global Advances in Business Studies, 2025)
In the digital era, smart tourism has gained significant prominence, revolutionising the tourism industry through advanced technologies that enhance efficiency, sustainability, and visitor experience. This study presents a bibliometric analysis of 531 documents on smart tourism published between 2014 and February 2025, using data from Scopus. The analysis is conducted using Microsoft Excel, BiblioMagika, OpenRefine, and VOSviewer to examine publication trends, influential studies, and emerging research themes. By leveraging bibliometric tools and leading academic databases, this research provides insights into the intellectual structure of smart tourism literature and identifies future research directions. The findings contribute to a deeper understanding of the evolution of smart tourism research, offering valuable implications for scholars and industry practitioners.